The Use of Indonesian Slang by Makassar Families in Their Daily Interaction - Umiyati Jabri; Ita Sarmita Samad (Majesty Journal, 2019)
This study aimed to identify the types of Indonesian slang used by Makassar families in their daily interaction. The study employed a descriptive qualitative design. The participants were six family members drawn from two Makassar families. Data were collected through audio recordings of naturally occurring conversations in the family setting. The recordings were transcribed and analyzed to identify slang forms appearing in daily speech. The findings revealed that Indonesian slang was frequently used by family members, while formal Indonesian was used less often in everyday interaction. Two major types of slang were identified, namely Jakarta slang and Makassarese slang. Jakarta slang appeared in forms such as tau, aja, banget, nggak, and kepo, which were generally derived from abbreviated or modified forms of standard Indonesian. Makassarese slang appeared in particles and suffixes such as -ta, -mi, -ji, -ka, and expressions such as pale and mentong, which reflected local linguistic influence. The study concludes that the daily speech of Makassar families is characterized by a combination of national urban slang and local Makassarese slang, with local slang being used more dominantly because of the speakers’ social and cultural environment.